2020
DOI: 10.1155/2020/4825767
|View full text |Cite
|
Sign up to set email alerts
|

Convolutional Neural Network for Seizure Detection of Nocturnal Frontal Lobe Epilepsy

Abstract: The Nocturnal Frontal Lobe Epilepsy (NFLE) is a form of epilepsy in which seizures occur predominantly during sleep. In other forms of epilepsy, the commonly used clinical approach mainly involves manual inspection of encephalography (EEG) signals, a laborious and time-consuming process which often requires the contribution of more than one experienced neurologist. In the last decades, numerous approaches to automate this detection have been proposed and, more recently, machine learning has shown very promisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…The advantage and disadvantages of the accelerometers method to detect the seizures is discussed in detail in (Nijsen et al, 2005; Nijsen et al, 2010) and authors revealed that this method requires less motor activity with better comfort to wear the device. In (Pisano et al, 2020), authors applied patient specific seizure detection using CNN which limits the time consumption for the doctors in classifying the EEG signal has seizure or not. Features learned by the convolution layers are applied directly to the transfer learning technique for fine tuning the CNN model.…”
Section: Introductionmentioning
confidence: 99%
“…The advantage and disadvantages of the accelerometers method to detect the seizures is discussed in detail in (Nijsen et al, 2005; Nijsen et al, 2010) and authors revealed that this method requires less motor activity with better comfort to wear the device. In (Pisano et al, 2020), authors applied patient specific seizure detection using CNN which limits the time consumption for the doctors in classifying the EEG signal has seizure or not. Features learned by the convolution layers are applied directly to the transfer learning technique for fine tuning the CNN model.…”
Section: Introductionmentioning
confidence: 99%
“…e model's first layer is composed of real EEG signals. e CNN model that follows after the input layer requires fourstep periods and eight filtering with 23 elements to conduct a combination on the original signal [26]. Extracted features of the carrier frequency are formed after the convolution process.…”
Section: E Rectified Linear Activation Unitmentioning
confidence: 99%
“…CNNs have achieved the remarkable results in the seizure detection, [44][45][46][47] the seizure control 48 and the detection of interictal epileptiform discharges. 49 A CNN model generally consists of convolution layers, pooling layers and fully connected layers.…”
Section: Convolutional Neural Network (Cnn)mentioning
confidence: 99%